Analysis of the Scientific Approach ‎to Islamic Religious Education ‎Learning ‎ - Cut Alya Zahrina; Sanusi Pane (el-Tarbawi : Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the scientific approach in Islamic religious education learning. The type of research used in this study is qualitative research. This study was conducted at SMP N 23 Rejang Lebong with the subjects of this study being all Islamic religious education teachers and students of SMP N 23 Rejang Lebong. Data collection techniques used were interviews, observation, and documentation. The data obtained were analyzed using data reduction, data display, and conclusion drawing/verification. The results of the study indicate that teachers' understanding, implementation, and evaluation of Islamic religious education learning using the scientific approach are good. Teachers' understanding of the scientific approach is evident from their knowledge of the steps and principles of the scientific approach. The implementation of learning using the scientific approach carried out by teachers is also in accordance with the steps of the scientific approach. Teachers observe students regarding what they will do, ask if there is a problem or there is material that is not clear, manage the class such as raising problems, asking students to explain what they understand, providing feedback, concluding and finally making connections to everyday life. The assessment or evaluation process in the scientific approach carried out by teachers has used authentic assessment where teachers make assessments on cognitive, affective and psychomotor aspects.